Multifactorial Determinants of Patient Satisfaction Among Medical and Surgical Patients at Nakuru Level 5 Hospital Amidst the Covid-19 Pandemic: A Cross-Sectional Study - Cheruto, Brendah; Suge, Valerie; Nthenya, Juliet; Peinan, Cynthia (East African Journal of Nursing, 2023)
Patient satisfaction is an indicator of quality health care provision and an outcome that is largely dynamic and multifaceted. It is an established standard that evaluates the achievement of patient’s needs and expectations. During the COVID-19 pandemic, patient care experienced unique challenges and concerns that were occasioned by the enforcement of stringent infection prevention and control measures. This study sought to assess determinants of patient satisfaction at Nakuru Level 5 Hospital amidst COVID – 19 pandemics. NL5H is one of the county’s teaching and referral hospitals in Kenya. A Descriptive cross-sectional design was adopted. Sixty-six randomly selected participants who comprised hemodynamically stable patients admitted in April and May 2022 were selected and interviewed. Data were collected and entered into Microsoft Excel 2019 and exported to SPSS version 24 for analysis. Descriptive statistics such as frequencies and percentages were used. Chi-square tests and logistic regression were used to assess factors associated with patients’ satisfaction. Of 66 participants, 51 (76%) were generally satisfied. Gender, education level, waiting time, health care workers’ communication behavior, patient referral, and level of patient trust had significant associations with patient satisfaction at p <0.05 level of significance. On patient-related factors, Female participants 58.8% (n= 51) were more satisfied though married male patients (41.1% n=51) who resided in urban areas and those earning less than Ksh.10,000 were least satisfied. At least 54.5% of n=66 paid cash to access health care. On healthcare-related factors 89.6% n=51 participants were satisfied with the availability of drugs in the facility however, 65.5% expressed dissatisfaction due to long waiting times of more than one hour and 65.7% lacked an explanation of their health status and treatment options by health care workers. On COVID-19 prevention factors, more than 92% reported satisfaction with the availability and adherence to infection prevention measures such as the availability of water and soap for handwashing, temperature checks at the hospital entry points, and maintenance of physical and social distancing. More than half, 64.2% of health care workers did not educate participants about COVID 19 and the importance of vaccination while 91% n=66 were not satisfied with the inadequate provision of masks to individual patients admitted in the wards. Among the 66 participants, only 41.8% had been vaccinated against COVID-19. Considering the findings, the institution should implement strategies such as the adoption of a standard emergency department triage protocol that would lead to effective sorting of patients and hence reduction of patient turnaround time. Regular customer satisfaction assessments and targeted customer feedback plans should be introduced in the hospital and health talk and COVID-19 vaccination campaigns will enhance awareness of COVID-19 disease prevention.